Analysis Of The Social Phenomenon Of Waste Management And The Implementation Of Waste Separation-Based Retribution Policy In Makassar City In Supporting The Green Economy - Daga, Rosnaini; Arief, Abd Samad; Haya, Rachmatan; Agriyani, Dody; Suyuti, Nurmadhani Fitri (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Waste management has become a crucial social and environmental issue in Makassar City, where the rapid growth of population and urban activities contributes significantly to the increase in waste generation. This study aims to analyze the social phenomena surrounding community behavior towards waste and to examine the implementation of waste separation-based retribution policies as part of the local government's strategy to support the green economy. The research employs a qualitative descriptive approach, combining interviews, observations, and documentation to explore public awareness, policy effectiveness, and institutional roles in waste management practices. The findings reveal that while public awareness of waste segregation is growing, the implementation of retribution policies still faces challenges, including limited socialization, inadequate facilities, and inconsistent enforcement. Strengthening community participation, optimizing local regulations, and enhancing collaboration between the Regional Research and Innovation Agency, the Environmental Office, and community-based organizations are essential to realize a sustainable waste management system. This study highlights the importance of integrating social, economic, and policy perspectives to promote a green economy through environmentally responsible waste management in Makassar City.